2018
DOI: 10.14283/jpad.2018.49
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Meaningfulness of Endpoints in the Generation Program by the Insights to Model Alzheimer’s Progression in Real Life (Imap) Study

Abstract: We are launching the Insights to Model Alzheimer’s Progression in Real Life study in parallel with the Alzheimer Prevention Initiative Generation Program. This is a 5-year, multinational, prospective, longitudinal, non-interventional cohort study that will collect data across the spectrum of Alzheimer’s disease. The primary objective is to assess the ability of the Alzheimer’s Prevention Initiative Cognitive Composite Test Score and Repeatable Battery for the Assessment of Neuropsychological Status to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…They incorporated risk factors and determinants of transition into their statistical models and explored the predictive ability of change on composite endpoints such as the APCC, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), the Clinical Dementia Rating Scale‐Sum of Boxes (CDR‐SB), amyloid burden, and APOE genotype. The iMAP was to be a 5‐year, multinational, prospective observational study of participants at‐risk for developing AD or who had mild cognitive impairment (MCI) or dementia due to AD 40 . The aim was to contribute to our understanding of different disease stages and define models of individual trajectories over the course of the disease.…”
Section: Measuring Clinical Meaningfulness In Alzheimer's Disease: Ho...mentioning
confidence: 99%
“…They incorporated risk factors and determinants of transition into their statistical models and explored the predictive ability of change on composite endpoints such as the APCC, the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS), the Clinical Dementia Rating Scale‐Sum of Boxes (CDR‐SB), amyloid burden, and APOE genotype. The iMAP was to be a 5‐year, multinational, prospective observational study of participants at‐risk for developing AD or who had mild cognitive impairment (MCI) or dementia due to AD 40 . The aim was to contribute to our understanding of different disease stages and define models of individual trajectories over the course of the disease.…”
Section: Measuring Clinical Meaningfulness In Alzheimer's Disease: Ho...mentioning
confidence: 99%
“…This may seem self-evident for clinical researchers but in fact, biomarker data are often missing also in more recent health economic and epidemiological studies. 5,17 Examining the subdomains or parts of EQ-5D we found that anxiety/depression was the first domain to be significantly affected in early stages of AD (see Figure 3). Pain/discomfort was also clearly affected but the impact seems smaller as this is a problem for many elderly, irrespective of symptoms.…”
Section: Study Conclusion and Disease Implicationsmentioning
confidence: 94%
“…We therefore recommend that biomarkers are collected, not only in epidemiological studies of patients with MCI but also in studies on health economic and patient‐reported outcomes, such as costs, caregiver burden, and quality of life. This may seem self‐evident for clinical researchers but in fact, biomarker data are often missing also in more recent health economic and epidemiological studies 5,17 …”
Section: Narrativementioning
confidence: 99%
“…Much of what we know about AD and biomarkers comes of course from clinics that commonly treat people who have had more than mild symptoms with more than very slow disease progression. The paper makes little note of variable trajectories, save that we know little about widespread amyloid testing as disease‐defining, especially without the Insights to Model Alzheimer's Progression in Real Life study 16 …”
Section: Some Specific Pointsmentioning
confidence: 99%
“…Much of what we know about AD and biomarkers comes of course from clinics that commonly treat people who have had more than mild symptoms with more than very slow disease progression. The paper makes little note of variable trajectories, save that we know little about widespread amyloid testing as disease‐defining, especially without the Insights to Model Alzheimer's Progression in Real Life study 16 Considering variable trajectories, if we are to accept the persuasiveness of the analogy with cancer, we should consider lessons might come from cancers that for many do not progress, such as thyroid cancer.…”
Section: Some Specific Pointsmentioning
confidence: 99%